STRATEGI PEMULIHAN DAN MITIGASI BENCANA LUMPUR LAPINDO DI SIDOARJO DALAM RANGKA MENINGKATKAN KEAMANAN NASIONAL - Ryan Fadhlur Fajri; Syamsul Maarif; Yuli Subiakto; Pujo Widodo; Kusuma (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
The Lapindo Mudflow disaster in Sidoarjo has caused widespread and prolonged economic, social and environmental impacts. To enhance national security, effective recovery and mitigation strategies are needed. This article discusses strategies that can be implemented in Lapindo Mud recovery and mitigation efforts, including inter-agency collaboration, infrastructure reconstruction, local economic development, improved preparedness, research and innovation development, community empowerment and public education. This research uses a qualitative literature review approach by analysing relevant data and information. The results show that a holistic and integrated recovery and mitigation strategy is needed to achieve better national security in the face of Lapindo Mud.